Pelatihan Peningkatan Skill Pelaku UMKM Dan Pengembangan Potensi Ekonomi UMKM Di Desa Wisata Bengkel Tabanan - Gusti Ayu Putu Eka Dewi Prihantari; Ida Bagus Putra Manuaba; I Gusti Ngurah Putra Harthawan; Ida Ayu Ria Paramita Handayani; Putu Diah Krisna Junitasari; Ketut Priya Premayanti (CV. Ulil Albab Corp, 2023)
Bengkel Village is a very strategic location to introduce rural tourism as well as various Subak activities and other cultural attractions that are still maintained. The selection of Bengkel Village as a location for community service is based on several aspects of the problem, namely, human resources and production and marketing. There are still many MSME actors who pay little attention to how to manage finances properly and MSME (Micro, Small, and Medium Enterprise) actors who still experience difficulties in distributing products (goods and services) and many have not maximized online marketing so that they can cover a wider target.The approach is carried out by providing training to the community in Bengkel Village, Kediri District, Tabanan Regency which is a smart village provided by the Ministry of Villages, namely the concept of a village based on digital and information technology. One of the efforts to maximize the potential is, starting from competency improvement training and how to market the products produced. The training provided is in the form of simple bookkeeping, tax calculation training, digital marketing strategy training for business development, and training on using social media as a promotional medium. This activity was attended by 15 MSME business actors in the Bengkel Village. Based on the results of the evaluation of community service activities, it can be concluded that the activities have been carried out in accordance with the needs and expectations of MSME actors in the Bengkel Tourism Village. Through this activity, it is hoped that the community can add insight so that the business is carried out in accordance with their respective plans and expectations.